2021
DOI: 10.1038/s41569-021-00569-6
|View full text |Cite
|
Sign up to set email alerts
|

PPAR control of metabolism and cardiovascular functions

Abstract: Peroxisome proliferator-activated receptor-α (PPARα), PPARδ and PPARγ are transcription factors that regulate gene expression following ligand activation. PPARα increases cellular fatty acid uptake, esterification and trafficking and regulates lipoprotein metabolism genes. PPARδ stimulates lipid and glucose utilization by increasing mitochondrial function and fatty acid desaturation pathways. By contrast, PPARγ promotes fatty acid uptake, triglyceride formation and storage in lipid droplets, thereby improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
225
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(286 citation statements)
references
References 187 publications
2
225
0
Order By: Relevance
“…The AMPK link was demonstrated between exercise and mitochondrial turnover with mitophagy activation, which helped refreshing the mitochondrial pool [98]. The effect of exercise, such as that of statins, can be considered as hormetic, since it causes transient elevation of ROS stimulating mitochondrial biogenesis and function (a process known as mitohormesis) but also improves mitophagy [99,100]. The increasing incidence of cardiovascular disorders can be attributed, at least partially, to the lack of exercise, which stimulates mitochondrial function, resulting in anti-inflammatory effect.…”
Section: The Mitochondrion As a Potential Therapeutic Targetmentioning
confidence: 99%
“…The AMPK link was demonstrated between exercise and mitochondrial turnover with mitophagy activation, which helped refreshing the mitochondrial pool [98]. The effect of exercise, such as that of statins, can be considered as hormetic, since it causes transient elevation of ROS stimulating mitochondrial biogenesis and function (a process known as mitohormesis) but also improves mitophagy [99,100]. The increasing incidence of cardiovascular disorders can be attributed, at least partially, to the lack of exercise, which stimulates mitochondrial function, resulting in anti-inflammatory effect.…”
Section: The Mitochondrion As a Potential Therapeutic Targetmentioning
confidence: 99%
“…In our study, H&E, Masson's trichrome, and Sirius red staining clearly reflected that Sch B could attenuate chronic liver injury and liver fibrosis, which indicated that Sch B is a potential compound for treating liver fibrosis. PPARγ is a nuclear receptor known for regulating glucose and lipid metabolism disorders (28,29). PPARγ also exerts antiinflammatory effects on immune cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…The essential transcription factor governing adipocyte biology is thought to be PPARγ [ 63 , 64 ]. Detailed information about PPARγ can be found in several excellent reviews [ 65 , 66 ]. In the present paper, we focus on the functions of PPARγ in adipose tissue in vivo.…”
Section: Known Transcriptional Regulators Of Adipogenesis In the Light Of In Vivo Studiesmentioning
confidence: 99%